Mechanical properties of triple blended concrete using fly ash and GGBS as cement replacement material for rigid pavements - Vijaya Gowri, T; Manjunath, B; Krishna Raju, C (International Journal of Engineering and Technology, 2018)
In the present investigations, Conventional Triple blended concrete (TBC)of 8 mixes were designed for M40 grade using w/b as 0.4 and tested for Compressive Strength and Flexural Strength. In these concrete mixes, Cement was replaced with 15% of Fly ash (FA)and with 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80% of Ground Granulated Blast Furnace Slag (GGBS), tested for 7 days and 28 days strength and compared with the strength of Conventional Concrete (CC). From the results, it was observed that, the strength of TBC is maintaining appropriate strength up to 50% GGBS replacement level and drastic decrease in strengths above 50% GGBS replacement level. The results are analyzed and the relations also developed between Compressive Strength and Flexural Strength of TBC for 7 days and 28 days.Â Â